Bispectral index in calves anesthetized with xylazine, midazolam, ketamine, isoflurane and subjected to continuous rate infusion of lidocaine - Araújo, Marcelo Augusto de; Beloti, Carolina Aparecida Carlin (UNESP); Deschk, Maurício (UNESP); Arruda, André Moreira Martins; Cheng, Lu Shi; Albuquerque, Verônica Batista de; Santos, Paulo Sergio Patto dos (UNESP) (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2015)
PURPOSE: To assess the bispectral index (BIS) and recovery in calves anesthetized with xylazine, midazolam, ketamine and isoflurane and subjected to CRI of lidocaine. METHODS: Xilazine was administered followed by ketamine and midazolam, orotracheal intubation and maintenance on isoflurane using mechanical ventilation. Lidocaine (2 mg kg-1 bolus) or saline (0.9%) was administered IV followed by a CRI (100 µg kg-1 minute-1) of lidocaine (L) or saline (C). Were recorded BIS, heart rate (HR), mean arterial pressure (MAP) and rectal temperature (RT) before administration of premedication (TB) and 15 minutes after (TX), before administering lidocaine (T0) and 20, 40, 60 and 80 minutes after the start of the CRI . Time do sternal recumbency (SRE) and standing (ST) and plasma lidocaine concentration also evaluated. RESULTS: In both treatments BIS decreased significantly at all times compared to TB. TX was higher than the subsequent times. HR decreased from baseline at all times and decreased from T40 in L compared to C. SRE was higher in L compared to C. CONCLUSIONS: Bispectral index values were consistent with the degree of hypnosis of the animals. Lidocaine did not potentiate isoflurane anesthesia assessed by BIS in unstimulated calves anesthetized with constant E´Iso. Lidocaine increased the time to sternal recumbency.
Keywords: Anesthesia, inhalation; Intermittent positive-pressure ventilation; Anesthesia recovery period; Chromatography; Cattle